PEMETAAN PARTISIPATIF POTENSI KECAMATAN TUNTANG KABUPATEN SEMARANG - Kurnianingtyas, Agnesia Putri; Arief Rahman, Ratna Ayu Permatasari (TEMATIK, 2021)
Tuntang is one district in Semarang Regency that has a strategic location and various potentials. But unfortunately, these potentials have not been recorded comprehensively, especially in the form of regional profile book. Based on the Regulation of the Minister of Home Affairs Number 12 of 2007 concerning Guidelines for the Compilation and Utilization of Village and Sub-District Profile Data, regional profiles contain various data related to demographic data, institutions, environment and natural conditions, to the potential and problems that exist in the area. However, the local government of Tuntang does not yet have sufficient capacity to compile an informative regional profile. Therefore, community service was carried out to help the local government of Tuntang to map the potential of their area and compile a regional profile book. The method used in the service activities for local government of Tuntang is participatory mapping. The participatory mapping activity is done by door to door technique with in-depth interviews with local government of Tuntang to help them understand better the conditions and potentials in their area. Furthermore, a field survey was conducted to verify the results of in-depth interviews. The data collected then being processed to be a profile book of Tuntang. The result of this community service activity is the increasing knowledge of local government of Tuntang about the conditions and potential of their area. In addition, other result is a profile book of Tuntang which contains geographical conditions, infrastructure conditions, economic conditions and regional potential, and a review of development policy of Semarang Regency in RTRW Kabupaten Semarang 2011-2031.